Donor funding and crowding out of public spending: Evidence from low and middle-income countries - Shine, Ritta Sabbas (Research of GSB, 2018)
In many low-resource settings agricultural output and public spending on agriculture are in decline, raising questions about the effectiveness of agricultural aid. To understand why these trends are occurring, we examined factors that affect the share of government spending on agriculture. Using a sample of 66 low- and middle-income countries from 1996-2010 we use dynamic panel regression models to explore: (1) the impact of agricultural aid on public expenditure to agriculture, and (2) the impact of aid on domestic resource mobilisation, which indirectly affects public expenditures. Our results provide evidence of a strong substitution effect, especially in low-income countries, suggesting aid to agriculture is treated as fungible. We also found evidence that aid loans resulted in higher tax revenues, while aid grants decreased tax effort, which may account for decreasing public investment in agriculture. To improve aid effectiveness, donors need to work with recipients to understand country needs and the fiscal environment of the receiving government.